A new solution to the "difficult problem" of the object of study of political economy. Issue 2 (10th December 2021) - Yang, Jiguo; Yuan, Renshu
Abstract : Purpose: As there are different interpretations of the object of study in the preface to the first edition of Capital (Volume I ) by Karl Marx, disagreements arise over the object of study on political economy, which becomes a "difficult problem." The purpose of the paper is to bring a new solution to the "difficult problem." Design/methodology/approach: Based on the analysis of the logic of the original text, the authors attempted to give a new interpretation of the "difficult problem" by analyzing the structure of Capital . The object of study of political economy is "the relations of production in the broad sense" of the capitalist mode of production. Findings: It comprises relations of production in the narrow sense and exchange relations in the broad sense, and the latter can be divided into exchange relations in the narrow sense and distribution relations. The three of them correspond to Volume I, II and III of Capital, respectively. Consumption in "the four-section theory" is not studied by the political economy. Originality/value: And the four-section theory is not a part of the theory of Marxist economics but a part of the classical economics criticized by Marx. Therefore, the object of study of socialist political economy with Chinese characteristics is "the relations of production in the broad sense" regarding the socialist mode of production with Chinese characteristics, which is different from the capitalist relations of production in the broad sense.